Acoso laboral en entidades estatales (2018)
"It is important because we must ensure the protection of the rights of public workers and even more so when there is a lack of knowledge about a rule that seeks protection with respect to situations of labor harassment such as Law 1010 of 2006. In practice there is ignorance of the norm, confusion, lack of commitment of officials and even fear of reporting such situations, based on the fact that workplace harassment comes from many perspectives. Since the beginning of labor relations there have been problems related to communication, treatment and, in general terms, all the fundamental aspects surrounding the link between the employee and the employer, given these circumstances it was necessary that within the system Colombian legal system will establish the appropriate mechanisms to avoid any abuse against the worker, which as a general rule, is the part that needs to be protected since it holds the position of least hierarchy within the labor nexus. Not only was it necessary to implement mechanisms that would allow access to the jurisdiction to people who were affected by this type of behavior, but also the need to develop comprehensive alternatives, with which it will be effectively solved, or at least diminish, the indexes of labor harassment, being the obligation of the legislator to establish the guidelines that compose this figure, the adequate procedures to make effective the rights that are in play and, above all, the preferential treatment to the people violated in their rights. Coupled with the fact that not only Colombian legislation has developed these tweets, international treaties on Human Rights, included through the Constitutionality Block (Article 93 CP), oblige the State to strive to combat this scourge. It is intended to provide the recommended approach, determine preventive actions, promote compliance with the law, among other forms or methods directed to state entities in order to effectively use this rule and at the same time improve the control of situations that have harmed some state workers On the part of the comrades, the possibility was raised of delimiting the situation of labor harassment specifically directed to a particular case, under this assumption it has been thought to look for a case within the armed forces specifically police or military force, where statistically they have been highlighted cases of labor harassment by superiors. Under the previous assumption, a given problem was also raised, starting with the compensation made by the respective entity and the analysis of how the entities should take out of their budget such compensation that repeat actions are made against those officials who have committed these behaviors against their subordinates."